Glycine encephalopathy in newborns and young children: global management standards and a clinical case - M.A. Gonchar; O.L. Logvinova; E.M. Pushkar; O.P. Pomazunovskaya; D.A. Ivakhnenko (Zaslavsky O.Yu., 2018)
The article shows a three-level approach to the diagnosis of glycine encephalopathy by the example of a clinical case. The article considers the modern etiology of the disease, based on molecular genetic testing of biallelic genes by DNA sequencing as well as the modern classification and peculiarities of the course of various forms of non-ketotic hyperglycinemia, differential diagnosis with other conditions and diseases accompanied by convulsions, and current principles of treatment of glycine encephalopathy.